Reclamation of formic acid wastewater by electro-oxidation coupled with UV irradiation (UV/EO) - Punnika Duangkaew; Songkeart Phattarapattamawong (Case Studies in Chemical and Environmental Engineering)
The research aims to reclaim formic acid wastewater using UV/EO process, compared with the electro-oxidation (EO). The UV/EO process was more effective in treatment of formic acid wastewater as the COD reduction was higher, compared with the EO alone. In addition, the UV/EO process could decrease TDS via conversion of chloride ions to chlorine. The UV/EO performance highly depended on current density (CD) and contact time, while the role of temperature was minor. The UV/EO performance was greatly enhanced with higher CDs in non-filtrated waters because of less interferences, compared with filtrated waters. Electrodes of BDD and titanium plates were robustness for the UV/EO process. The estimated treatment costs were approximately 0.5, 1.3, and 2.4 US dollar/m3 for CD at 5, 10 and 15 mA/cm2, respectively. The UV/EO process has the potential to reclaim formic acid wastewater for non-potable application. The treated water is suitable for reuse in plantation, irrigation, and cleaning, as the total coliform and fecal coliform counts were inactivated to non-detectable levels. However, pH and TDS should be monitored. This is the first study that conducts the UV/EO experiment with industrial formic acid wastewater. The finding indicates that UV/EO is an effective process for reclamation of formic acid wastewater.